ACTIONS TO SUPPORT THE YOUTH OF UZBEKISTAN - Mukhtarov Sardorbek Saidullo son; Mamajonova Gulmira Dilbek daughter; Gayratova Gulzoda San'at daughter (International Journal of Human Computing Studies, 2020)
In this article, we talk about how the Kamolot youth social movement came into being and its role in the implementation of reforms in Uzbekistan. It is true that today the name of this organization, the principles of its work have changed, but as an organization that has done a lot in its time and has played an invaluable role in the choice of many young people. Carried out its activities. We have tried to cover this in our article